Development of the Japan Science and Technology Agency Index of Competence to Assess Functional Capacity in Older Adults: Conceptual Definitions and Preliminary Items. (12th October 2015) - Iwasa, Hajime; Masui, Yukie; Inagaki, Hiroki; Yoshida, Yuko; Shimada, Hiroyuki; Otsuka, Rika; Kikuchi, Kazunori; Nonaka, Kumiko; Yoshida, Hiroto; Yoshida, Hideyo; Suzuki, Takao
Improvement in the health of older people and changes in their lifestyles necessitate a scale that can better measure their competence at a higher level. This study describes the development process of the Japan Science and Technology Agency Index of Competence (JST-IC) by (a) refining conceptual definitions and developing preliminary items and (b) examining the basic properties of the items. Participants were 1, 253 septuagenarians (539 men and 714 women) living in communities, who were asked to judge whether they were independent via 88 items. To examine the basic properties of the preliminary items, five different analyses were conducted. Thirty-four items were considered as inappropriate (6 overlapped between the analyses): (a) 9 due to very high or low ratios of responders who answered "yes, " (b) 4 due to gender or regional differences, (c) 5 due to their weak association with health status, (d) 9 due to low communalities in factor analysis, and (e) 13 due to redundancy of meaning with other items. Conceptual definitions and preliminary items were developed, and the basic properties of the items were examined to create the JST-IC. The next step would be to screen the remaining 54 items to create the final version of the scale.